Field tolerance of ginger (Zingiber officinale) genotypes to soft rot under rainfed up- land situation - D K Dash, A Mishra, S K Mohanty, B Behera, (Journal of Spices and Aromatic Crops, 2008)
Eleven genotypes of ginger were screened for reaction to soft rot and rhizome yield at AICRPon Dryland Agriculture (OUAT), Phulbani, Orissa during 2006-07. The trial was laid out inRBD with three replications. The crop was planted during last week of June at the site whereturmeric was grown in the previous year. Soft rot incidence in ginger was recorded at 60, 75,90 and 135 days after planting (DAP). Over 8% soft rot incidence was found in ACC-35,ACC-117 and SG-666 at 60 DAP. These genotypes had severe soft rot incidence at 135 DAP.No observation on soft rot was made after 135 DAP due to senescence of some plants for dryweather. The genotypes showing minimum soft rot were Suprabha, Phulbani Local andVIC-8. Soft rot incidence was very high in ACC-117 and no yield was realized from thisgenotype. Due to severe soft rot incidence, premature drying of plants was observed in somegenotypes. Rhizome yield varied from zero (ACC-117) to 46.27 q/ha (VIC-8). However, rhizomeyields of Suprabha, VIC-8 and Phulbani Local were found to be at par. Poor performance ofdifferent genotypes was attributed to dry weather during peak growth stage and soft rotincidence.